1998
DOI: 10.1001/jama.279.9.657
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and Other Risk Factors for Excessive Warfarin Anticoagulation

Abstract: Context.-Warfarin is highly effective in preventing thromboembolism, but increases the risk of hemorrhage, particularly at an international normalized ratio (INR) greater than 4.0. Identifying causes of excessive anticoagulation in clinical practice could help target patients at risk for elevated INRs. Objective.-To determine causes of INRs greater than 6.0 in a clinical practice setting. Design.-Case-control study. Setting.-Outpatient anticoagulant therapy unit. Patients.-Outpatients followed up prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
2
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(166 citation statements)
references
References 34 publications
2
154
2
8
Order By: Relevance
“…The mechanism of this interaction has only recently been elucidated (Thijssen et al, 2004) and likely results from the independent inhibitory effect of an acetaminophen metabolite on enzymes of the vitamin K cycle. Although several case reports and controlled studies have reported that acetaminophen potentiates the anticoagulant effect of warfarin (Hylek et al, 1998), others have not found a clinically relevant interaction (Fattinger et al, 2002). NSAIDs such as mefenamic acid (Holmes, 1966) etodolac (Ermer et al, 1994;ibuprofen (Penner and Abbrecht, 1975) and tenidap (Apseloff et al, 1995) may also displace coumarin anticoagulants from protein binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this interaction has only recently been elucidated (Thijssen et al, 2004) and likely results from the independent inhibitory effect of an acetaminophen metabolite on enzymes of the vitamin K cycle. Although several case reports and controlled studies have reported that acetaminophen potentiates the anticoagulant effect of warfarin (Hylek et al, 1998), others have not found a clinically relevant interaction (Fattinger et al, 2002). NSAIDs such as mefenamic acid (Holmes, 1966) etodolac (Ermer et al, 1994;ibuprofen (Penner and Abbrecht, 1975) and tenidap (Apseloff et al, 1995) may also displace coumarin anticoagulants from protein binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…This interacttion is proposed to be due to inhibition of its metabolism and interference with formation of clotting factors. Gingival bleeding and hematuria were observed in case reports when paracetamol is given with warfarin (Hylek et al, 1998). However, due to lack of a safer alternative, paracetamol is still the analgesic and antipyretic of choice in patients receiving warfarin therapy, as long as excessive amounts and prolonged administration are avoided (Shek et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…31.8). The analysis by Hylek et al shows a relationship between higher paracetamol doses and greater anticlotting efficacy of warfarin [5]. The catch is that this relationship was found in those who had higher INR values, so the moral of the story is that the sensitive should avoid high-dose paracetamol if they take warfarin.…”
Section: Choosing Drugs To Treat Nociceptive Painmentioning
confidence: 99%
“…Observational studies demonstrate that the risk of intracranial hemorrhage rises dramatically at INR values of 4.0–5.0 [64]. Factors leading to INRs >6.0 are medications known to potentiate OAC (table 2), advanced malignancy, recent diarrhea and taking more oral anticoagulants than prescribed [65]. …”
Section: Risk Factors For Bleeding Complicationsmentioning
confidence: 99%